Do elite athletes experience low back, pelvic girdle and pelvic floor complaints during and after pregnancy? - Boe, K.; Backe-Hansen, K. L. (Scandinavian Journal of Medicine & Science in Sports, 2006)
The aim of the present investigation was to study prevalence of low back pain, pelvic girdle pain (PGP) and pelvic floor disorders during pregnancy and after childbirth in elite athletes. A postal questionnaire was sent to all elite athletes who had given birth registered with The Norwegian Olympic Committee and Confederation of Sports (n=40). Eighty age-matched women served as the control group. The response rates were 77.5% and 57.5% in the elite athletes and control groups, respectively. There were no significant differences in the prevalence of low back and PGP, urinary or fecal incontinence among elite athletes and controls at any time point. The prevalence of low back pain without radiation to the leg in elite athletes was 25.8%, 18.5%, 9.7% and 29% the year before pregnancy, during pregnancy, 6 weeks postpartum and at the time of completing the questionnaire, respectively. The prevalence of PGP was 0, 29.6%, 12.9% and 19.4%. Prevalence of stress urinary incontinence was 12.9%, 18.5%, 29% and 35.5%. None of the elite athletes had fecal incontinence at any time point. There were no differences in mode of delivery or birthweight between elite athletes and controls. The elite athletes had a significantly lower body mass index at 6 weeks postpartum and at present compared with the control group.